2004
DOI: 10.5694/j.1326-5377.2004.tb06442.x
|View full text |Cite
|
Sign up to set email alerts
|

How does mental health status relate to accessibility and remoteness?

Abstract: Objective: To determine whether mental illness is associated with accessibility and remoteness. Design: A cross‐sectional, population‐based, computer‐assisted telephone interview survey, stratified by Accessibility and Remoteness Index of Australia (ARIA) categories. Setting: Secondary analysis of data collected from 2545 South Australian adults in October and November 2000. Outcome measures: Psychological distress and depression as determined by the Kessler 10 Psychological Distress Scale, the SF‐12 measure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 12 publications
0
24
0
Order By: Relevance
“…In a study of non-metropolitan areas of New South Wales, Kelly et al found lower mean K10 scores in remote areas than in very remote or inner or outer regional areas; mean scores were similar for males and females [38]. Although non-significant, a similar trend was evident in South Australia with lower mean K10 scores in accessible/moderately accessible areas compared to highly accessible and remote/very remote areas [39]. In the US, Dhingra and colleagues found that, among those in the 2007 Behavioral Risk Factor Surveillance System (BRFSS) (with a landline telephone), urban residents were more likely than rural residents to have mild (K6 7-12 out of 24) or serious (K6 13+) psychological distress after adjustment for socio-demographic characteristics [40].…”
Section: Discussionmentioning
confidence: 96%
“…In a study of non-metropolitan areas of New South Wales, Kelly et al found lower mean K10 scores in remote areas than in very remote or inner or outer regional areas; mean scores were similar for males and females [38]. Although non-significant, a similar trend was evident in South Australia with lower mean K10 scores in accessible/moderately accessible areas compared to highly accessible and remote/very remote areas [39]. In the US, Dhingra and colleagues found that, among those in the 2007 Behavioral Risk Factor Surveillance System (BRFSS) (with a landline telephone), urban residents were more likely than rural residents to have mild (K6 7-12 out of 24) or serious (K6 13+) psychological distress after adjustment for socio-demographic characteristics [40].…”
Section: Discussionmentioning
confidence: 96%
“…The questionnaire chosen for NESDA is composed of the 10 questions of the Kessler-10 (K-10) , and fi ve additional questions asking for the presence (yes/no) of a panic attack, social phobia, agoraphobia, general anxiety or nervousness, and psychotropic medication use during the last month ( Table 1). The K-10 is a short self-administered scale used for the detection of psychological distress, and has been applied in large epidemiologic studies (Eckert et al, 2004). It has proven screening qualities for affective disorders (Furukawa et al, 2003;Kessler et al, 2003).…”
Section: Screening Stages and Instrumentsmentioning
confidence: 99%
“…Although the majority of literature found an association with urbanicity and higher rate of mental health problem as described above, Peters & Jackson (2005) reported several studies in which no conclusive evidence of an association with urban/ rural residence could be found for psychiatric morbidity (Romans-Clarkson et al 1990;Blazer et al 1994;Parikh et al 1996;Eckert et al 2004).…”
Section: Introductionmentioning
confidence: 96%